Spectropolarimetry of the Type IIb SN 2008aq. Issue 2 (20th June 2016) - Stevance, H F; Maund, J R; Baade, D; Höflich, P; Patat, F; Spyromilio, J; Wheeler, J C; Clocchiatti, A; Wang, L; Yang, Y; Zelaya, P
ABSTRACT: We present optical spectroscopy and spectropolarimetry of the Type IIb SN 2008aq 16-d and 27-d post-explosion. The spectrum of SN 2008aq remained dominated by Hα P Cygni profile at both epochs, but showed a significant increase in the strength of the helium features, which is characteristic of the transition undergone by supernovae between Type IIb and Type Ib. Comparison of the spectra of SN 2008aq to other Type IIb SNe (SN 1993J, SN 2011dh, and SN 2008ax) at similar epochs revealed that the helium lines in SN 2008aq are much weaker, suggesting that its progenitor was stripped to a lesser degree. SN 2008aq also showed significant levels of continuum polarization at p cont = 0.70 (±0.22) per cent in the first epoch, increasing to p cont = 1.21 (±0.33) per cent by the second epoch. Moreover, the presence of loops in the q − u planes of Hα and He i in the second epoch suggests a departure from axial symmetry.